Performance Appraisal of Non-governmental Organizations: A Discussion on Pakistan 2010 Floods Response and Recovery - A. Ali; N. Baig; A. Khan (ASEAN Journal on Science and Technology for Development, 2013)
The paper examines in detail the role of NGOs (Non-governmental Organizations) in response and recovery phase of a disaster. Donors, INGOs (International Non-governmental Organizations) and NGOs work for the betterment of affected community but due to certain shortfalls, the community did not benefit as much as intended. In this research those gray areas are highlighted in detail through field visits and interaction with the community devastated by 2010 floods. Lack of inter-agency cooperation, partnership with inexperienced local NGOs and lack of transparency and accountability mechanisms are those areas which reduce the effectiveness of response and recovery efforts. These gray areas cause loss of precious resources and duplication of efforts which results in increased vulnerability of that particular community.